SYSTEM OF WORK TO OVERCOME RESTRICTIONS OF THE TEACHER DURING THE PROCESS PROFESSIONAL RETRAINING PEDAGOGICAL STAFF (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the system of pedagogical berries and proposes the ways of solving o f this problem.